Development of a systems approach to assess organisational adequateness - Silva, J.; Manjate, J. (Systemic Approaches in Social Structures, 6th National & International HSSS Conference, 2010)
This paper proposed a systems view to address a research design aiming at discussing the adequateness of the organisational structure of a firm along time. The approach was closely related to the complex nature of the situation and it would focus on the contribution of the design parameter IS/IT to the formalisation of the firm structure. Actually, Enterprise Systems might provide a significant impact in decision making, either by contributing to enhance control, or to information transparency, because structure effectiveness depends on the internal coherence between the design parameters and the contingency factors. So, relevant information systems should contribute to the alignment and coordination of organisational activities, to the creation of relationships among businesses, to the systematic search of business opportunities. This proposal set a few research questions, about the definition of an adequate conceptual model to discuss the problem-situation, about the role of information systems within the structure, about the usefulness of enterprise systems best practice and, about its acceptance by the public limited companies of Mozambique. In fact, the practical grounds for the exercise concerned the path pursued by a State-Owned Enterprise from Mozambique since the independence of the country in 1975 by checking which structure changes have occurred with PETROMOC. The conceptual model would, then, be used as a way to reconstruct a sequence of Past events providing a base for longitudinal ordered questioning and so, searching paths to explain and discuss the future. Thus, PETROMOC will provide a base to empirically test the usefulness of the conceptual model. To sum up, the Soft Systems Methodology was proposed as the way to operationalise the systems view in a useful method that might provide original, relevant, updated and unusual contributions to the design of enquiries concerning complex organisational situations. This might become a step further, to test and develop the mid range theory proposed by Vilas-Boas (2009b), in order to find adequate organisational structures to strategic business development.